REVIEW OF THE WEB AT THE CLASS I IMMIGRATION OFFICE OF BORDER CONTROL PEKANBARU ON THE DECREE OF THE MINISTER OF LAW AND HUMAN RIGHTS NO M. HH-01TI.01.05 TAHUN 2016 ABOUT THE STANDARDIZATION OF WEB IN MINISTRY OF LAW AND HUMAN RIGHTS - Sandy Ariandani (Polteknik Imigrasi, 2020)
The development of the globalization era which is quite significant at this time has resulted in several innovations that are very helpful for human performance in everyday life. This innovation also develops in the field of immigration services which is formed in the use of information technology which includes the concept of good and clean governance. All forms of information that will be provided to the public have been packaged properly in the form of a website. The page-based service includes all information and services in the field of immigration at an Immigration Office. This study aims to provide a result of a review of the suitability of the immigration service page at the Immigration Office referred to by the standardization of the page as stated in the Ministry of Law and Human Rights number M. HH-01.TI.01.05 of 2016 concerning Standardization of Pages within the Ministry of Law and Human Rights of the Republic of Indonesia.